DUKUNGAN SOCIAL DAN KECENDERUNGAN DEPRESI POST PARTUM PADA IBU PRIMIPARA DI DAERAH GEMPA BANTUL - Urbayatun, Siti (Universitas Ahmad Dahlan, 2010)
This research examined a correlation between Social Support and Post Partum Depression. Quantitatif analytical test was done by application of SPSS 15.00 for Windows software. The subject of this research were 60 primipara mother at RB Bina Sehat and RSKIA Ummi Khasanah, Bantul, Yogyakarta. The result of this research indicates that: There was significantly negative correlation between Social Support and Post Partum Depression. (r = -0.545, p= 0.00, p<0.00). The contribution of Social Support for Post Partum Depression was 29,7 %.